Sagot :
[tex]\large{\mathcal{SOLUTION:}}[/tex]
- 2x²+8x-10 = 0
- 2x²+8x = 10
- 2(x²+4x) = 10
- 2(x²+4x+4) = 10+2(4)
- 2(x+2)² = 10+8
- 2(x+2)² = 18
- 2(x+2)² /2 = 18/2
- (x+2)² = 9
extracting square root
- √(x+2)² = √9
- x+2 = ± 3
[tex] \\ [/tex]
For , x+2 = 3
- x+2 = 3
- x = 3 - 2
- x = 1
For , x+2 = -3
- x+2 = -3
- x = -3-2
- x = -5
Therefore , the solutions are 1 and -5
[tex] \\ [/tex]
[tex]\large{\mathcal{ANSWER:}}[/tex]
- 1 and -5
[tex] \\ [/tex]
✒️[tex]QUESTION[/tex]
Find the solution of the equation 2x² + 8x - 10 = 0 by completing the squarez?
=============================
✒️[tex]ANSWER[/tex]
x = 1 or x = -5
=============================
✒️[tex]SOLUTION[/tex]
Solve By Factoring :
2x² + 8x - 10 = 0
2x² - 2x + 10x - 10 = 0
2x ( x - 1 ) + 10 ( x - 1 ) = 0
2 ( x - 1 ) ( x + 5 ) = 0
x - 1 = 0 or x + 5 = 0
x = 1 or x = -5
So the correct answer is x = 1 or x = -5